Pengaruh Penempatan Kerja terhadap Kepuasan Kerja Karyawan PT Waskita Sriwijaya Tol - Jerry Angga; Agustina Hanafi; Parama Santati (PKP Fakultas Syariah LPPM IAI Nasional Laa Roiba, 2023)
This study aims to determine the effect of job placement on job satisfaction of employees of PT Waskita Sriwijaya Tol. The independent variable in this study is job placement and the dependent variable is job satisfaction. The method used in this research is quantitative. The population in this study were employees at PT Waskita Sriwijaya Tol, totaling 61 employees. As well as the sample of this study using a saturated sample so that the sample is the entire population of 61 employees. The data collection method used in this study is primary data obtained from questionnaires. The analysis technique used is simple linear regression analysis. The data obtained were tested using validity test, reliability test, simple linear regression test, analysis of correlation coefficient (r) and coefficient of determination (R2), as well as hypothesis testing or t test. The test was carried out using the statistical package for social science (SPSS) version 21. Based on the results of the analysis, it was concluded that work placement had a significant effect on job satisfaction of PT Waskita Sriwijaya Tol employees. Keywords: Work Placement; Job satisfaction